Pengujian Desalinasi Surya Tipe Single Basin Double Slope Kemiringan 45° Dengan Porositas Sumbu Serap 0,20 mm Pada Kapasitas 8 Liter - Fikri Fahlevi Nasution; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Due to the very rapid population growth, the need for clean water will continue to increase year by year. This makesthe availability of clean water a major issue today, especially for coastal people. Coastal residents have to buy cleanwater in their daily lives, and coastal residents also use rainwater. However, the availability of clean water still existsin nature. In the dry season, it is very difficult to get clean water. One solution to this lack of clean water is to obtainclean water by desalination. Desalination of seawater is the process of maintaining clean water by removing excesssalt from the water and using sunlight to create freshwater. This study describes an experimental study of theefficiency of solar desalination plants using solar energy. The experiments was performed with a sponge pore size of0.2 mm and an initial volume of 8 liters. With an average solar radiation of 719.9 W/m2, the desalinated air producedis 2.944 kg and the efficiency is 25.15%.Keywords : Solar Desalination, Porosity, Sponge